The Distribution of Charged Amino Acid Residues and the Ca2+ Permeability of Nicotinic Acetylcholine Receptors: A Predictive Model - Fucile, Sergio (Frontiers in Molecular Neuroscience, 2017)
Nicotinic acetylcholine receptors (nAChRs) are cation-selective ligand-gated ion channels exhibiting variable Ca2+ permeability depending on their subunit composition. The Ca2+ permeability is a crucial functional parameter to understand the physiological role of nAChRs, in particular considering their ability to modulate Ca2+-dependent processes such as neurotransmitter release. The rings of extracellular and intracellular charged amino acid residues adjacent to the pore-lining TM2 transmembrane segment have been shown to play a key role in the cation selectivity of these receptor channels, but to date a quantitative relationship between these structural determinants and the Ca2+ permeability of nAChRs is lacking. In the last years the Ca2+ permeability of several nAChR subtypes has been experimentally evaluated, in terms of fractional Ca2+ current (Pf, i.e. the percentage of the total current carried by Ca2+ ions). In the present study, the available Pf values of nAChRs are used to build a simplified modular model describing the contribution of the charged residues in defined regions flanking TM2 to the selectivity filter controlling Ca2+ influx. This model allows to predict the currently unknown Pf values of existing nAChRs, as well as the hypothetical Ca2+ permeability of subunit combinations not able to assemble into functional receptors. In particular, basing on the amino acid sequences, a Pf > 50% would be associated with homomeric nAChRs composed by different alpha subunits, excluding alpha7, alpha9 and alpha10. Furthermore, according to the model, human alpha7beta2 receptors should have Pf values ranging from 3.6% (4:1 ratio) to 0.1% (1:4 ratio), much lower than the 11.4% of homomeric alpha7 nAChR. These results help to understand the evolution and the function of the large diversity of the nicotinic receptor family.